Prevalence of psychoactive substance use in men who have sexual relationships with men, Colombia - Bedoya Mejia, Sebastián; Cardona Arango , Doris; Agudelo Cifuentes, Maite Catalina; Ramos-Jaraba, Sara Milena; Matagira-Rondón, Giselly; Segura-Cardona, Ángela M; Berbesí-Fernández, Dedsy Yajaira (Revista Cuidarte, 2024)
Highlights • There is a high prevalence of consumption of psychoactive substances, especially alcohol, marijuana, and popper. • Popper is one of the psychoactive substances that is emerging among the population; it must be carefully monitored. • The consumption of psychoactive substances is statistically and epidemiologically associated with having casual couples and sexual work. • The consumption of psychoactive substances increases the probability of having unprotected sexual intercourses. Introduction: The use of psychoactive substances (PS) in the population is a current problem that affects a large part of humanity, with diverse consequences. Objective: To analyze the factors associated with the consumption of PS among men who have sex with other men (MSM) in three Colombian cities. Material and Methods: This cross-sectional descriptive study used the respondent-driven sampling (RDS) method and obtained a sample of 1301 MSM. The association between the sociodemographic and personal characteristics and the consumption of PS was assessed using the chi-square test. Prevalence ratios were calculated along with their 95% confidence intervals. For the multivariate analysis, a Poisson regression with a log link and robust estimator was employed to explore the factors associated with PS use. Result: The prevalence of consumption of PS in the last year was 87%, prevailing the consumption of alcohol, marijuana, and poppers. Having occasional partners (PR: 0.44; 95% CI 0.29 - 0.67), attending public places or establishments such as bars and saunas (PR: 3.39; 95% CI 2.34 - 4.91), sex work, and not using a condom in the last sexual encounter (PR: 2.10 95% CI 1.37 - 3.22) are factors associated with the use of these substances. Discussion: There is evidence of a high prevalence of recreational use of PS, even higher than that found in the general population. Conclusion: A high prevalence and association with risky sexual behaviors is confirmed, which requires promotion and prevention actions to reduce the use of these substances. How to cite this article: Bedoya Mejia Sebastián, Cardona Arango Doris, Agudelo Cifuentes Maite Catalina, Ramos-Jaraba Sara Milena, Matagira-Rondón Giselly, Segura-Cardona Ángela M, Berbesí-Fernández Dedsy Yajaira. Prevalence of psychoactive substance use in men who have sexual relationships with men, Colombia. Revista Cuidarte. 2024;15(2):e3477. https://doi.org/10.15649/cuidarte.3477